A complete genome sequence for Pseudomonas syringae pv. pisi PP1 highlights the importance of multiple modes of horizontal gene transfer during phytopathogen evolution. (22nd May 2019) - Baltrus, David A.; Clark, Meara
Summary: Hybrid assembly strategies that combine long‐read sequencing reads from Oxford Nanopore's MinION device combined with high‐depth Illumina paired‐end reads have enabled completion and circularization of both plasmids and chromosomes from multiple bacterial strains. Here we demonstrate the utility of supplementing Illumina paired‐end reads from a previously published draft genome of P. syringae pv. pisi PP1 with long reads to generate a complete genome sequence for this strain. The phylogenetic placement and genomic repertoire of virulence factors within this strain provides a unique perspective on virulence evolution within P. syringae phylogroup 2, and highlights that strains can rapidly acquire virulence factors through horizontal gene transfer by acquisition of plasmids as well as through chromosomal recombination.